Studi Kasus : Penerapan Resistance Exersice untuk Meningkatkan Sirkulasi Perifer pada Pasien Diabetes Mellitus Tipe II - Wulandari, Ayu; Damayantie, Netha; Sativa Yan, Loriza (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2025)
Type 2 Diabetes Mellitus (T2DM) is one of the most common chronic metabolic diseases found in the community and can lead to microvascular complications such as peripheral circulation disorders. This study aimed to describe nursing care for patients with type 2 diabetes mellitus through the application of Resistance exercise as a non-pharmacological intervention to improve peripheral circulation. This study used a case study design with a descriptive approach. The research was conducted from May to June 2025 in the working area of Putri Ayu Public Health Center, Jambi City. The intervention was given to two patients who experienced sensory symptoms such as tingling and foot pain, along with an Ankle Brachial Index (ABI) value of less than 1. Resistance exercises were performed for three consecutive days using a theraband, with five movements in each session. Each session lasted approximately 10–15 minutes per day. Evaluation results showed improvements in peripheral circulation, indicated by increased ABI values and a reduction in sensory complaints. Resistance exercise can be used as one of the nursing care approaches to help prevent peripheral complications in patients with type 2 diabetes mellitus.